Development of an AI-Assisted Mobile Point of Sales and E-Commerce System with Real-Time Inventory Synchronization - Maulana Irfan; Miftakhul Ushbah Nastaftian; Hermawan Sentyaki Sarjito; Jonathan; Irham Maulana Johani; Muhammad Nasir; Aditya Wicaksono (Universitas Suryakancana Cianjur, 2026)
Indonesian micro, small, and medium enterprises (UMKMs) face significant operational bottlenecks due to their reliance on manual and fragmented sales and inventory management systems. To address these challenges, this research designs, develops, and evaluates PasPOS, an integrated mobile Point of Sales (POS) and E-Commerce system tailored for Indonesian micro-retailers, utilizing Toko Mpok Nani as an implementation case study. Developed chronologically using the Agile Scrum framework across eight sprints, the platform implements a decoupled microservices architecture. This infrastructure consists of a centralized Laravel 12 backend API and Flutter-based Admin and Member applications, all synchronized through an 11-table relational database. Furthermore, the Admin App integrates an edge computer vision-based barcode scanning feature to accelerate cashier transactions using standard smartphone cameras. System validation via User Acceptance Testing (UAT) using a structured Likert-scale questionnaire yielded an overall average score of 4.44 out of 5.00 for the Admin App and 4.43 for the Member App, classifying both as